Proceedings - Natural Language Processing in a Deep Learning World 2019
DOI: 10.26615/978-954-452-056-4_102
|View full text |Cite
|
Sign up to set email alerts
|

Term Based Semantic Clusters for Very Short Text Classification

Abstract: Very short texts, such as tweets and invoices, present challenges in classification. Although term occurrences are strong indicators of content, in very short texts, the sparsity of these texts makes it difficult to capture important semantic relationships. A solution calls for a method that not only considers term occurrence, but also handles sparseness well. In this work, we introduce such an approach, the Term Based Semantic Clusters (TBSeC) that employs terms to create distinctive semantic concept clusters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…In such cases, recent NLP methods, e.g. (Paalman et al, 2019), can be used to extract information from these texts, which can subsequently be incorporated as additional features in the model.…”
Section: Resultsmentioning
confidence: 99%
“…In such cases, recent NLP methods, e.g. (Paalman et al, 2019), can be used to extract information from these texts, which can subsequently be incorporated as additional features in the model.…”
Section: Resultsmentioning
confidence: 99%
“…The Word2Vec model considers the context and the semantic meaning of the words. So if two words are close in meaning they will be located close in the space (Mikolov, 2013). With the transformation of words to vectors, the machine-learning algorithms can perform algebra operations on them.…”
Section: Modelingmentioning
confidence: 99%
“…Recent research in topic estimation in the context of open-ended questions (OEQ) has revealed that short texts covering not only responses to OEQ, but also huge volumes of text involved in interactions with social networks and the language of business stressed the need to develop specific algorithms for this class of texts (Burrows et al, 2015;Galhardi & Brancher, 2018;Paalman et al, 2019;Poulimenou et al, 2016;Zhang et al, 2019) [29][30][31][32][33].…”
Section: Related Workmentioning
confidence: 99%